Neuromodulation of Hippocampal Synaptic Plasticity, Learning, and Memory by Noradrenaline - Gelinas, J. N.; Nguyen, P. V. (Central Nervous System Agents in Medicinal Chemistry, 2007)
Neuromodulators are chemical substances that modify neural responses without directly triggering synaptic excitation. They broadly impact multiple brain functions, such as arousal, sleep, attention, perception, learning, and memory. The noradrenergic neuromodulatory system widely innervates the mammalian brain, including the hippocampus. Hippocampal synaptic plasticity is believed to importantly contribute to the formation and consolidation of some types of memory. Stimulation of noradrenergic receptors in the hippocampus alters neuronal excitability and synaptic plasticity, suggesting a key role for noradrenaline (NA) in learning and memory. Consistent with this notion, NA enhances memory for a variety of hippocampus-dependent tasks. The effects of NA receptor activation on cellular plasticity may account for NA-dependent modulation of memory in the hippocampus. Furthermore, dysfunction of the noradrenergic neuromodulatory system contributes to numerous cognitive and psychiatric disorders. Determining how NA influences information processing at cellular and behavioural levels is essential for understanding the physiology of memory. Such understanding may also reveal new strategies to improve treatments for human memory disorders.
Keywords: LTP (long-term potentiation)